LENGTH-WEIGHT RELATIONSHIP OF INTERTIDAL MOLLUSCS FROM MUMBAI, INDIA - Kulkarni, B. G.; Jaiswar, A. K. (Journal of Indian Fisheries Association, 2015)
A study on the length-weight relationship of common intertidal molluscsfrom Mumbai showed a high degree of correlation between their length andweight. Most of the molluscs exhibited isometric growth pattern but in somespecies, allometric growth was found, which is attributed to maturity, nonlineargrowth of shell and the ecological conditions. The variations in thegrowth rate of Gafrarium divaricatum sampled from two geographicallyseparate sites, Bandstand and NCP A, is a result of variation in eco~ogicalconditions.Key words: Length-weight, intertidal 1nolluscs